Analysis of the impact on the sewage sludge treatment community by means of wetlands and vermicomposting and the production of fertilizer: systematic review (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
The sludge generated in wastewater treatment plants is an element of great importance due to the pollutants that constitute it and its potential impact on the environment. Therefore, it is important to investigate new technologies that can treat these biosolids with less impact and convert them into usable products, such as fertilizers. This article presents a review of the important aspects of the treatment of sewage sludge by means of wetlands and vermicomposting processes to obtain a material that can be applied to agricultural soil. Initially, information concerning the origin and composition of sewage sludge is presented. Subsequently, important aspects to consider in the treatment of sludge are mentioned, followed by an individual explanation of the treatments using wetlands and vermicomposting. Finally, the integrated treatment of wetlands and earthworms is described. At the end, conclusions and possible future research concerning the topic addressed in the article are drawn.